Crisis management in the time of COVID-19: Zoom on its impact on the Moroccan economy and the general government budget (What happened, what was done and what’s to be done) - EL MOUISSIA , Imane; BENABDELHADI, Abdelhay (Revue Internationale du Chercheur, 2022)
In 2020, Covid-19 started as a small outbreak in rural Wuhan China, grew to take a pandemic size and proportions. Due to the highly contagious nature of the disease, many governments issued draconian stay at home mandates and travel bans, as a way to stop the rapid spread of the virus. Which delt a powerful blow to the economy, from severe disruptions of the international supply chains, to the crash of the financial markets. Morocco, like every other nation, suffered great loss, because of the interconnectivity of the world’s economy, this crisis had severe repercussions on the imports and exports between the kingdom and the rest of the world. On a domestic level, covid-19 put a damper on demand, caused the bankruptcy of many businesses and contributed to the collapse of the entire tourism sector. This paper will endeavor to present how the government used crisis management to save to take charge of the situation. As well as the effects of this crisis on the Moroccan economy, highlighting the toll it took on its public.